A cidade ideal - Ana Aragão (In_Bo, 2020)
A perspective animated of monuments, in which iconic architectures are melted in a summa of urban models designed, imagined, sometimes ephemeral, often desired. It is a collage of references, even before of cities and architectures, starting with the format and the main street in explicit dialogue with the humanistic tables. Ana Aragão’s cidade ideal evokes the central themes of urban theory. The relationship between model and architecture is central: each architecture can be, as a projection of the individual dwelling, summaries and units of measurement of the city model, where domestic distribution and urban infrastructure coincide or overlap. It is the architecture of the city. The illustration also highlights the theme of stratification, the synchronized co-presence of models developed over an extended time frame. Conflicting, overlapping, even excluding and intercutting models. A carpet composed of heterogeneous urban models by type and history, that appear in a continuum to form urban complexity. Thus, the perspective is readable through heterogeneous behaviours, both active or passive: from the designer (or the enchanted and passionate student) able to identify the vast range of architectural quotations, to the urban dweller who can live the drawing as a passenger or a temporary tourist, without a necessary specialised critical conscience. What is left in daily narratives that support or convey ideals and models?